2013
DOI: 10.1371/journal.pone.0054326
|View full text |Cite
|
Sign up to set email alerts
|

Sediment Bacterial Communities Reflect the History of a Sea Basin

Abstract: How entire microbial communities are structured across stratified sediments from the historical standpoint is unknown. The Baltic Sea is an ideal research object for historical reconstruction, since it has experienced many fresh- and brackish water periods and is depleted of dissolved oxygen, which increases the sediment's preservation potential. We investigated the bacterial communities, chemical elements (e.g. Cr, Pb Na, P, Sr and U) and sediment composition in a stratified sediment core dated by radiocarbon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
13
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 42 publications
5
13
1
1
Order By: Relevance
“…Generally, batch cultures are known to be selective for fast-growing opportunistic bacteria, including Gammaproteobacteria (Eilers et al, 2000;Fuchs et al, 2000), and therefore, our results can be seen as a cultivation artefact. Nevertheless, Gammaproteobacteria are generally abundant members of sediment communities, both in freshwater and marine systems, including deep sediments Ye et al, 2009;Szabo et al, 2011), as well as Littorina Sea phase sediments from the Baltic Sea (Lyra et al, 2013). Thus, we do not see our results as a mere cultivation artefact but as evidence for a recruitment of marine bacteria from these very old sediments under the right conditions, even though we primarily enriched habitat generalists which can tolerate a broad range of salinities at the expense of habitat specialists that occur exclusively in marine systems.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, batch cultures are known to be selective for fast-growing opportunistic bacteria, including Gammaproteobacteria (Eilers et al, 2000;Fuchs et al, 2000), and therefore, our results can be seen as a cultivation artefact. Nevertheless, Gammaproteobacteria are generally abundant members of sediment communities, both in freshwater and marine systems, including deep sediments Ye et al, 2009;Szabo et al, 2011), as well as Littorina Sea phase sediments from the Baltic Sea (Lyra et al, 2013). Thus, we do not see our results as a mere cultivation artefact but as evidence for a recruitment of marine bacteria from these very old sediments under the right conditions, even though we primarily enriched habitat generalists which can tolerate a broad range of salinities at the expense of habitat specialists that occur exclusively in marine systems.…”
Section: Resultsmentioning
confidence: 99%
“…Emeis et al, 2003;Andr en et al, 2011). It has been shown that such fluctuations can be followed in the composition of sediment bacteria at different depths (Lyra et al, 2013). However, it has not been demonstrated whether those bacteria are viable and able to grow under suitable environmental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Family Anaerolineaceae consists mainly of anaerobic fermenters [80][82] that have been found mostly in organic-rich environments such as anaerobic methanogenic sludges [80], [82], [83] or sediments [24], [84]. Recently, various anaerolineacean bacteria were detected in deep-core layers covering the last 8000 years of the Baltic Sea [85], which suggests that they may contribute to organic matter mineralization processes in the deeper biosphere. There are studies in which H 2 -producing Anaerolineaceae strains grew more rabidly in the presence of hydrogenotrophic methanogens [80], [82], [83].…”
Section: Discussionmentioning
confidence: 99%
“…This shift was caused by gradual cooling and increased precipitation across northern Europe, which decreased the salinity and increased the winter ice cover of the Baltic Sea, resulting in marked changes in Baltic Sea diatom and bacterial communities and an overall decrease in primary productivity (Tuovinen et al 2008;Sepp€ a et al 2009;Witkowski et al 2009;Lyra et al 2013;Willumsen et al 2013). We hypothesize that the cooling was a major factor driving the reproductive isolation between North Sea and Baltic Sea grey seals: the former adjusting their breeding season and habitat to ice-free conditions in the North Sea, and the latter to a colder environment with annual periods of sea ice.…”
Section: The Role Of Climate and Humans In Subspecies Divergencementioning
confidence: 99%